Application of Surfactants in Commercial Crop Production for Water and Nutrient Management in Sandy Soil - Guodong Liu; Gene McAvoy; Ben Hogue; Crystal A. Snodgrass (EDIS, 2019)
This 6-page article provides an overview of surfactants and how they may be used to better manage water and nutrients in sandy soils for vegetable and fruit production. It is a minor revision written by Guodong Liu, Gene McAvoy, Ben Hogue, and Crystal A. Snodgrass, and published by the Horticultural Sciences Department, October 2019.